The mystery of Edgar Allan Poe - Haffner, Craig; Lusitana, Donna F.; Morowitz, Noah (A%E Television Networks, 1994)
Explores the life of Edgar Allan Poe, touching on his childhood, his failure as a student at West Point and the violence in his life that later reflected itself in his work.